Effect of Flaxseed Gum and Konjac Gum on the 3D Printing Properties of Pea Protein Isolate Emulsion Gels - Congjin BAI; Jingjing GUO; Yifan WANG; Zhenrong LI; Bo JIAO; Lei DAI (Shipin gongye ke-ji)
To develop plant-based protein 3D-printed food suitable for patients with swallowing difficulties, this study explored the use of a composite polysaccharide comprising flaxseed gum and konjac glucomannan at a mass ratio of 2:3. The composite polysaccharide was combined with pea protein isolate (PPI) under shearing treatment to investigate the effects of different concentrations (0.5%, 0.7%, 0.9%, 1.1%, and 1.3%) on the particle size, rheological properties, and 3D printing performance of emulsion gels. Additionally, the emulsion gels were evaluated using the International Dysphagia Diet Standardization Initiative (IDDSI) framework. The results indicated that the composite polysaccharide exhibited varying effects on the improvement of emulsion gels depending on its concentration. Particle size analysis revealed a decreasing trend in the particle size of PPI emulsion gel with increasing polysaccharide concentration. Rheological properties showed that the addition of polysaccharides endowed the gels with viscoelastic properties, as evidenced by G' > G'' for all samples. At a concentration of 1.1%, the emulsion gel exhibited the smallest particle size, the highest G' and G'' values, and optimal viscoelasticity. Furthermore, the printed structures displayed the most distinct textures, stable frameworks, and superior printing adaptability. The IDDSI evaluation indicated that emulsion gels containing 1.1% and 1.3% polysaccharides could be classified as Level Ⅳ transitional foods. In conclusion, the composite polysaccharide at a concentration of 1.1% significantly enhanced the 3D printing performance of PPI-based emulsion gels, providing a theoretical basis for developing plant-based 3D printing inks.